The Expansionary Lower Bound : Contractionary Monetary Easing and the Trilemma - Cavallino, Paolo (IMF Working Papers; Working Paper, 2018)
We provide a theory of the limits to monetary policy independence in open economies arising from the interaction between capital flows and domestic collateral constraints. The key feature of our theory is the existence of an 'Expansionary Lower Bound' (ELB), defined as an interest rate threshold below which monetary easing becomes contractionary. The ELB can be positive, thus acting as a more stringent constraint than the Zero Lower Bound. Furthermore, the ELB is affected by global monetary and financial conditions, leading to novel international spillovers and crucial departures from Mundell's trilemma. We present two models under which the ELB may arise, the first featuring carry-trade capital flows and the second highlighting the role of currency mismatches.